Historical Memory as a Component of Society’s Value-Normative System - Alaverdyan, Nelli (Bulletin of Yerevan University E: Philosophy, Psychology, 2024)
The article deals with the issues of historical memory, the factors that form it, and the main forms of manifestation and transmission mechanisms. Historical memory was considered from two perspectives. first, the philosophy of historical memory can be considered as a part of the biophilosophy of a person who carries memory, knows himself and evaluates its content, secondly, historical memory is important as a factor for mobilizing the "valuable potential of society" to respond to the challenges of our time. Taking into account the challenges faced by modern society, the article paid special attention to the possibilities of the approach called "technological determinism", which makes one realize the need for "technological breakthrough" as a condition for the survival of the country, and which can be a corresponding "turning point" in historical consciousness and historical for memory. It is about the historical experience of implementing scientific and technological "breakthroughs" and mobilizing the creative potential of society to solve vital problems. Historical memory is one of the important components shaping political behavior and consciousness. It makes the past a real value, a significant part of our life and a driving force for the most important social events. Historical memory, with its energy, drives society to certain institutionalized behaviors, and divides historical space and time. In this process, the decoding and revaluation of historical memory is an important prerequisite for ensuring the continuity and vitality of the normal transformation of society.